ANALISIS DAERAH UTAMA HASIL TANGKAPAN GURITA DAN DISTRIBUSI HASIL TANGKAPAN GURITA DI KABUPATEN SIMEULUE - Selya Fatimah; Agus Naufal; Faisal Syahputra (JURNAL KREASI RAKYAT, 2025)
Simeulue Regency, located in the Aceh Province hold significant potencial in octopus (Octopus Sp) fisheries. This study aims to identify the main octopus producing areas, analyze the factors affecting catch levels, and describe the distribution patterns of octopus landings in Simeulue. A quantitative method was applied through surveys, interviews, field observations, and statistical, data analysis. The results show that the highest production comes from three sub-districts. Teupah Selatan, Alafan and Teluk Dalam, contributing approximately 86% of the total catch. Seasonal patterns, marine conditions, and traditional fishing gear influence catch levels. The distribution involves several marketing challenges include limited transportation infrastructure and logistical accsess to external markets, which affect product quality and the price received by local fishers.